Analysis of Thai shapes & forms from Thai arts to create further creations in Thai contemporary graphic design. - Pittayamatee, Pairoj (DEC Journal : Art and Design, 2022)
Thai shapes & forms is one of the elements that has usually been applied into a graphic design piece to give the impression of Thai. However, the knowledge about Thai shapes & forms from Thai Arts has rarely been analyzed and collected. The first stage of this research was to collect Thai arts which appear to have geometric square shapes & forms: triangular, rectangular and circular, as the main subjects. Then analyzed the origin and interpretation of those shapes & forms before classifying them into groups and simplifying them to line arts. The next stage was to gather existing graphic design pieces that gave the impression of Thai and also contained Thai shapes & forms based on the classified groups from the first stage. They were used as evidence of deploying Thai shapes & forms from Thai Arts to give the impression of Thai. The study resulted in categories, origin, and interpretation of Thai shapes & forms in Thai art as follows. Triangular shapes & forms from Chomhae referred to the Buddha, Sumeru Mountain, and Traiphum. Sintao lines represented story divider and time dimensions. The round shapes & forms from the Dharma Chakra represented the Dharma. The ceiling star pattern represented the heavens. The pattern in the middle of the Buddha’s footprint implied the Buddha. The square shapes & forms from the pattern of the guards referred to the four Buddhist communities. Twelve wooden recesses referred to monks in Buddhism. Applying Thai shapes & forms from Thai Arts in a graphic design work may conserve Thainess reflecting the identities of the nation. Simplifying Thai shapes & forms from Thai arts to simple graphic line arts combined with theory and knowledge in graphic design will definitely expand the boundary of creativity in Thai contemporary graphic design with no limit.